Republic of Moldova : Request for a Three-Year Arrangement Under the Extended Credit Facility and Request for an Extended Arrangement. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses Moldova's request for a Three-Year Arrangement under the Extended Credit Facility and request for an Extended Arrangement. The economy remained overregulated and hampered by relative price distortions. High barriers to entry and low competition in telecommunications, trade, and food processing have kept domestic prices significantly above international prices of many consumer products. In contrast, utility tariffs generally remained well below cost-recovery levels, leading to substantial arrears and underinvestment. The crisis and pre-election spending hikes resulted in a large increase in the fiscal deficit.